Organizations as Carriers of Status and Class Dynamics: A Historical Ethnography of the Emergence of Bordeaux's Cork Aristocracy - Grégoire Croidieu; Walter W. Powell (Emerald Publishing Limited, 2024)
This paper seeks to understand how a new elite, known as the cork aristocracy, emerged in the Bordeaux wine field, France, between 1850 and 1929 as wine merchants replaced aristocrats. Classic class and status perspectives, and their distinctive social closure dynamics, are mobilized to illuminate the individual and organizational transformations that affected elite wineries grouped in an emerging classification of the Bordeaux best wines. We build on a wealth of archives and historical ethnography techniques to surface complex status and organizational dynamics that reveal how financiers and industrialists intermediated this transition and how organizations are deeply interwoven into social change.
10.1108/S0733-558X20240000090006; 10.1108/S0733-558X20240000090006; Sociological Thinking in Contemporary Organizational Scholarship; EBP109300890